2021
DOI: 10.1136/bmjopen-2020-047770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prematurity on long-term renal health: a systematic review

Abstract: ObjectiveTo investigate the literature and determine if prematurity has an impact on long-term adverse kidney outcomes.DesignSystematic review.Data sourcesOVID Medline, PubMed, SCOPUS, CINAHL and EMBASE databases were searched for studies relating to the adverse outcomes of prematurity from 1990 to April 2021.Eligibility criteria for selecting studiesAll articles published between January 1990 and April 2021 that investigated whether premature infants developed long-term adverse renal outcomes were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Prematurity is also likely linked to increased risk of kidney dysfunction and high BP in childhood and into early adulthood. Premature birth was found to confer a two-fold increased risk of CKD [46,47]. Our current study also analyzed renal function, as several literature reviews have highlighted prematurity and/or LBW as a marker of impaired nephrogenesis and is related to chronic kidney disease (CKD).…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity is also likely linked to increased risk of kidney dysfunction and high BP in childhood and into early adulthood. Premature birth was found to confer a two-fold increased risk of CKD [46,47]. Our current study also analyzed renal function, as several literature reviews have highlighted prematurity and/or LBW as a marker of impaired nephrogenesis and is related to chronic kidney disease (CKD).…”
Section: Discussionmentioning
confidence: 99%
“…Although increased rates of renal dysfunction or chronic kidney disease in their later life has been shown in premature infants, there are no reports in the literature addressing the coexistence of proteinuria and ROP development [17]. It has been found that prematurity and low birth weight are associated with fewer nephrons and lower glomerular density [18].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on the effect of prematurity on long-term kidney health found that prematurity is likely linked to an increased risk for renal dysfunction and elevated/high BP in childhood and into early adulthood. Extremely premature birth conferred a threefold increase in the risk of CKD, whereas premature birth conferred a twofold increase in the risk of CKD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%